2021
DOI: 10.3390/ijerph18168392
|View full text |Cite
|
Sign up to set email alerts
|

Living with the Late Effects of Childhood Cancer Treatment: A Descriptive Qualitative Study

Abstract: Long-term childhood cancer survivors (CCS) may experience physical, social, and emotional struggles posttreatment. Our aim was to explore the experiences of CCS dealing with the late effects of cancer treatment from their own perspectives. This study employed a qualitative descriptive design to explore and describe the experience of dealing with late effects among CCS. Semi-structured interviews were conducted with 15 CCS in Korea. Participants were selected by purposive and snowball sampling and individually … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 55 publications
1
2
0
Order By: Relevance
“…Another study found similar results in long‐term childhood cancer survivors (age 19 to 39). Additionally, these survivors showed considerable understanding of their physical strength levels and found an appropriate balance between activities and rest and replenished their energy when they felt tired, which is in line with our results (Hong et al, 2021 ).…”
Section: Discussionsupporting
confidence: 92%
“…Another study found similar results in long‐term childhood cancer survivors (age 19 to 39). Additionally, these survivors showed considerable understanding of their physical strength levels and found an appropriate balance between activities and rest and replenished their energy when they felt tired, which is in line with our results (Hong et al, 2021 ).…”
Section: Discussionsupporting
confidence: 92%
“…Childhood cancer can have a long-lasting impact on survivors, as individuals may experience physical, social, and mental stress post-treatment when they are young adults [ 35 , 36 ]. Our findings are important as the psychological well-being of families is associated with resilience, or the ability to adapt and function when facing adversity [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…To distillate recovery resources from an ecological point of view, the overarching categories in the coding frame were predefined and consisted of the three levels of recovery capital, namely personal, social, and community recovery capital [ 11 , 31 ]. Upon familiarization with the data, the subcategories emerged through an iterative process of open (i.e., inductive coding of relevant aspects in the interviews separately) and axial coding (i.e., identifying commonalities and grouping together subthemes) [ 32 ]. To increase the validity of the research and to enhance intercoder reliability [ 33 ], the first two authors independently coded and categorized five rich interviews into a coding framework.…”
Section: Methodsmentioning
confidence: 99%